Síntese e avaliação da atividade biológica de neolignanas e análogos - Souza, Vanessa Almeida de (Universidade Federal de São Carlos, 2012)
Substituted benzofurans and neolignans have considerable pharmacological potential. In this work, we report some synthetic methods for the construction of these rings, as well as their derivatives. Through the oxidative coupling reaction between isoeugenol, some neolignans were obtained. Employing the McMurry and Sonogashira cross coupling, Wittig-Horner olefination or condensation of 2- hydroxyacetophenones with bomoacetophenones led to the formation of different benzofurans. The biological activities of the obtained compounds were evaluated against the microorganisms of Chagas disease, leishmaniasis and tuberculosis, and also against the Trypanosoma cruzi gGAPDH enzyme. The neolignans showed better activity against epimastigote forms of T. cruzi, and one of the compounds showed a very close activity when compared to the standard benznidazole. The neolignans also showed good results against promastigote forms of Leishmania amazonensis, with IC50 values below 26 μM; and activity against Mycobacterium tuberculosis with MIC of 31.25 μM for compounds 66, 70 and 73. The benzofurans were, in general, more active against the L. amazonensis than T. cruzi. The benzofurans also showed interesting activity against the M. tuberculosis, with MIC of 15.12 μM for compound 97. All compounds tested showed no activity against the gGAPDH enzyme.
Keywords: Síntese orgânica; Neolignanas; Atividade biológica; Doença de Chagas; Leishmaniose; Tuberculose; CIENCIAS EXATAS E DA TERRA::QUIMICA